Modified Advancement Flaps a Promising Approach for the Pilonidal Sinus Surgery - Qassim jabber Muhammad; Dr. Adel Mosa Alrekabi; Rusel Kamal Abed (American Journal of Biomedicine and Pharmacy, 2025)
Background: Pilonidal sinus disease, a chronic inflammatory disease, affects sacrococcygeal soft tissue, especially in young adults. The ideal treatment for Pilonidal sinus disease stays divergence. Aim of the study: the purpose of this study was to share the findings of the Modified advancement flap technique surgery combined with vacuum‐assisted closure for treating Pilonidal sinus disease. Method: This prospective study was conducted from January 2022 to October 2024 in Al- Diwaniyah Teaching Hospital, the study included 63 patients with mean age of 17.44±3.02 years range (15-28) mostly were below 20 years, 52 (82.5%). Males were 40 (63.5%) more common than females 23 (36.5%). Under general anesthesia, all patients underwent modified advancement flap with vacuum‐assisted closure. The patient's, surgical time, hospital stay, post operative hematoma, necrosis, and recurrence rate were recorded. The visual analogue scale (VAS) score and the Vancouver scar score were used to score patients' pain and scars in the surgical area. Results: Mean operative time was 34.21±4.23 minutes range between (30-40), mean healing time was 14.44±0.64 days range between (14-16), while mean duration of drain removal was 14.0±0.0 days among patients, no patients were lost to follow‐up. None of the patients experienced post‐operative recurrence Post operative pain score was 3.49±0.50 range between (3-4), scar score was range between 3.39±0.97 (6-8), while cosmetic effect score was 8.08±0.70 range between (7-9). Conclusions: Modified advancement flap surgery is an effective and innovative method for the treatment of Pilonidal sinus disease, with no recurrence rate and rapid recovery.